METHODOLOGY OF USING DIDACTIC GAMES AND DIFFERENT METHODS TO IMPROVE THE QUALITY OF MATHEMATICS EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article describes the use of didactic games and various non-traditional methods in mathematics lessons, as well as their importance and effectiveness passed. In the teaching of mathematics, teachers should have the skills to organize the lesson process in non-traditional ways, to achieve the design of the educational process based on a perfect model, and to use these projects wisely. It can be a guarantee of the formation of practical skills and qualifications in them. It is thought that the interest in science will increase and it will lead to an increase in the quality of education.